Functional changes in the vanilloid receptor subtype 1 channel during and after acute desensitization - Novakova-Tousova, K; Vyklicky, L; Susankova, K; Benedikt, J; Samad, A; Teisinger, J; Vlachova, V (Neuroscience, 2007)
Agonist-induced desensitization of the transient receptor potential vanilloid receptor-1 (TRPV1) is one of the key strategies that offer a way to alleviate neuropathic and inflammatory pain. This process is initiated by TRPV1 receptor activation and the subsequent entry of extracellular Ca(2+) through the channel into sensory neurones. One of the prominent mechanisms responsible for TRPV1 desensitization is dephosphorylation of the TRPV1 protein by the Ca(2+)/calmodulin-dependent enzyme, phosphatase 2B (calcineurin). Of several consensus phosphorylation sites identified so far, the most notable are two sites for Ca(2+)/calmodulin dependent kinase II (CaMKII) at which the dynamic equilibrium between the phosphorylated and dephosphorylated states presumably regulates agonist binding. We examined the mechanisms of acute Ca(2+)-dependent desensitization using whole-cell patch-clamp techniques in human embryonic kidney (HEK) 293T cells expressing the wild type or CaMKII phosphorylation site mutants of rat TRPV1. The nonphosphorylatable mutant S502A/T704I was capsaicin-insensitive but the S502A/T704A construct was fully functional, indicating a requirement for a specific residue at position 704. A point mutation at the nearby conserved residue R701 strongly affected the heat, capsaicin and pH-evoked currents. As this residue constitutes a stringent CaMKII consensus site but is also predicted to be involved in the interaction with membrane phosphatidylinositol 4,5-bisphosphate (PIP(2)), these data suggest that in addition to dephosphorylation, or as its consequence, a short C-terminal juxtamembrane segment adjacent to the transient receptor potential box composed of R701 and T704 might be involved in the decelerated gating kinetics of the desensitized TRPV1 channel.
Keywords: membránové potenciály; Dose-Response Relationship, Drug; metoda terčíkového zámku; vztah mezi dávkou a účinkem léčiva; Rats; transformované buněčné linie; teplota; transfekce; TRPV Cation Channels; Cell Line, Transformed; Phosphatidylinositol 4,5-Diphosphate; vápník; kapsaicin; mutace; fosfatidylinositol-4,5-difosfát; Patch-Clamp Techniques; Membrane Potentials; krysa rodu Rattus; Calcium; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Mutation; zvířata; vztahy mezi strukturou a aktivitou; Humans; Temperature; kationtové kanály TRPV; proteinkinasa závislá na vápníku a kalmodulinu typ 2; Transfection; elektrická stimulace; Capsaicin; Electric Stimulation; Structure-Activity Relationship; lidé; Animals